Improving Quality of Financial Reporting Through Good Government Governance and Effectiveness of Internal Audit - Kewo, Cecilia Lelly; Mamuaya, Nova Ch (International Journal of Economics and Financial Issues, 2019)
Issue that has arisen today in the management of public administration is good governance. Good governance can enhance organizational leadership, management and supervision, produce more effective interventions, and ultimately lead to better outcomes with improved community life. One of the form of government governance is financial statement accountability. The purpose of this study to provide empirical evidence regarding the effects of government governance and the effectiveness of internal audits on quality of financial statements. Sources of data obtained through field research conducted through observation, interviews and questionnaires and literature study. Data collection was conducted from March to July 2019 at the offices of regional work units in 8 districts / cities in the province of North Sulawesi, Indonesia. Returns the questionnaire at 58% of the amount distributed. Data collected were analyzed using Structural Equation Modeling with the path analysis method approach. The results showed that with an error rate of 0.05, good governance partially had a positive effect on the quality of the financial statements, the effectiveness of internal audit had a positive effect on the financial statements. Simultaneously good governance and the effectiveness of internal audit have a positive effect on the quality of local government financial reports. Keywords: Good Governance, Internal Audit, Quality of Financial Reporting JEL Classifications: M41, H70, G38 DOI: https://doi.org/10.32479/ijefi.8734